Indonesian students’ perceived benefits of the micro-teaching course to their teaching internship - Zulfikar, Teuku; Nidawati, N.; Khasinah, Siti; Mayangsari, Indah (Universitas Pendidikan Indonesia, 2020)
This study aims to explore student-teachers’ perceptions of the benefits of micro-teaching class they have attended to their teaching internship. It also seeks to identify the most and the least likely aspects of teaching which have been sufficiently covered in the micro-teaching course. The participants of this study were ten senior EFL students at a State Islamic University in Indonesia who have taken a micro-teaching class and teaching internship program. The data from interviews and students’ written narratives reveal that these students perceive the micro-teaching class to be sufficiently helpful in their teaching internship phase. These students developed their basic pedagogical skills. They become more confident; develop communication skills, and most importantly, the micro-teaching class has helped them develop questioning skills. However, students’ interviews and written narratives also indicate that management skills, such as classroom and time management, and skills to write lesson plan are the least likely aspect of teaching covered during the micro-teaching class, which then become obstacles for them during their teaching internship.